밥 중심 식사가 마우스의 체중 및 혈중 지질 함량에 미치는 영향 - 최원희(Won Hee Choi); 엄민영(Min Young Um); 안지윤(Ji Yun Ahn); 정창화(Chang Hwa Jung); 서정숙(Jung Sook Seo); 하태열(Tae-Youl Ha) (東아시아食生活學會誌, 2013)
This study was designed to evaluate the effect of a rice-based diet on body weight and serum lipid levels. Thirty male C57BL/6 mice were randomly divided into three groups and fed a high-fat diet (HFD), rice-based diet (RD), or bread-based diet (BD) for five weeks. Our results showed that the RD group had a significantly lower final body weight, although there was no significant difference in daily food intake among the groups. There was a reduction in body weight gains, adipose tissues weight, and adipocyte size of epididymal adipose tissue in the RD group (p<0.05). Also, serum triglycerides and total cholesterol in the RD group were significantly decreased compared to the BD group. RD also reduced fasting glucose and insulin levels. These results indicate that the intake of RD attenuates increases in body weight and serum lipid concentrations in mice, suggesting its benefits for the dietary control of obesity and hyperlipidemia. 본 연구는 밥 중심 식사 패턴이 비만에 미치는 영향을 조사하고자 C57BL/6 마우스를 고지방식이 대조군(HFD), 밥 중심 식사 급여군(RD) 및 빵 중심 식사 급여군(BD)으로 분류하여 각 실험 식이를 5주간 공급하여 마우스의 체중 변화, 혈중 지질 함량, 지방조직의 무게 및 혈중 glucose 및 insulin 함량을 비교 측정하였다. 실험 결과, 모든 처리군에서 사료 섭취량의 유의적인 차이를 나타내지 않았으나, RD 급여군에서의 체중 증가량은 BD 급여군에 비하여 유의적으로 낮아졌다(p<0.05). 지방조직 무게 역시 RD 급여군에서 낮은 수치를 보였으며, 특히 부고환지방의 무게 및 지방세포의 크기는 BD 급여군에 비하여 현저하게 감소하였다. RD 급여군에서의 혈중 중성지방 및 총콜레스테롤, 포도당 및 인슐린 농도 역시 BD 급여군에 비하여 유의적으로 낮았다(p<0.05). 이상의 실험 결과를 종합해 볼 때, 밥 중심의 식사는 고지방 식이를 비롯한 빵 중심 식사에 비하여 체내 지방조직의 축적을 억제하고, 혈중 지질농도를 감소시키며, 혈당의 증가를 억제함으로써 비만 및 당뇨병 등의 대사성 질환을 개선하는 데에 있어서 효과적인 것으로 사료된다.